Hank the Cowdog : The Case of the Lost Camp - Book 77 - Erickson, John R., 1943- (Perryton, TX : Maverick Books, Inc., 2021)
"Slim Chance is in a bad mood. In fact, he's been in a bad mood for a few months now, and it looks like it might become a permanent condition. The ranch has been in the middle of one of the worst droughts it's ever seen, and when the clouds do finally decide to let down a little rain, the last thing Slim wants to hear is that Deputy Kile got more rain than he did. Things are looking pretty bleak until Little Alfred asks his dad to take him fishing, and Slim winds up having to go in Loper's place. However, to everyone's surprise, the camping expedition turns out to be more exciting than Little Alfred had anticipated, including some great fishing and a bit of unexpected weather!"--back cover.
Keywords: Dogs -- Juvenile fiction; Ranch life -- Juvenile fiction. -- West (U.S.); Droughts -- Juvenile fiction; Camping -- Juvenile fiction; Western stories; Dogs -- Fiction; Ranch life -- Fiction. -- West (U.S.); Droughts -- Fiction; Camping -- Fiction; Juvenile fiction